Analisa Perbandingan Algoritma Bubble Sort, Insert Sort dan Selection Sort - Agus Heri Yunial (Jurnal Informatika Universitas Pamulang, 2025)
The algorithm in a program describes the flow or sequence of the program. A good program must have a good algorithm, where an algorithm is said to be good, one of which is the best use of time in processing the program. A sorting algorithm is an algorithm that carries out the sorting process in the program. Some existing sorting programs include bubble sort, insert sort and selection sort. In this research, the processing time of the three algorithms will be compared in sorting 100-10,000 random data both ascending and descending which are arranged in 15 combinations of data sequences. The sorting process is carried out using the C++ programming language. From the test results it was found that for fully random data the bubble sort algorithm performs the longest sorting process and the selection sort algorithm performs the process with the fastest average time and for almost sorted data the bubble sort algorithm performs the longest sorting process and the insert sort algorithm performs the process with the fastest average time